Students' Perceptions of Using TikTok @Nofreeadi for Vocabulary Acquisition: A Qualitative Study - Tari, Yosefa Kaldista; Musyarofah, Lailatul; Aisyah, Siti (Journal of English Development, 2026)
The integration of social media into English as a Foreign Language (EFL) learning has opened up new opportunities for vocabulary acquisition among students. This study explores students' perceptions of using the TikTok account @nofreeadi as a medium for learning English vocabulary. Using a qualitative descriptive approach, it involved twelve students from the English Education program. Data were collected through questionnaires and semi-structured interviews, then analyzed using thematic analysis. The findings revealed four main themes: ease of use, perceived usefulness, factors limiting acceptance, and user expectations. Students viewed TikTok @nofreeadi as an easy-to-use platform due to its short, clear, and interesting content, as well as its usefulness in supporting vocabulary learning through contextual examples. However, several limitations were identified, including the fast delivery of content, limited depth of explanation, and minimal interaction. Overall, the research results indicate that TikTok @nofreeadi serves as a fairly effective complementary medium for vocabulary learning, underscoring the importance of strategically integrating TikTok-based learning into formal English as a Foreign Language (EFL) instruction to enhance students' vocabulary development.